Reducing Early Adolescent Risk Behaviors through Indonesia’s PIK-R Counseling Program - Aswini Aswini; Muh Fahrurrozi; Armin Subhani (IJE : Interdisciplinary Journal of Education, 2026)
This study examines the effectiveness of a school-based counseling intervention, the Youth Information and Counseling Center (Pusat Informasi dan Konseling Remaja, PIK-R), in reducing risk behaviors among early adolescents in Indonesia. A quasi-experimental design with a non-equivalent control group was applied to sixth-grade primary school students aged 11-12 years. The experimental group received a six- to eight-week PIK-R intervention consisting of peer education, guided counseling, role-playing, group discussion, and case-based learning, while the control group continued regular school activities. Data were collected using a validated Likert-scale questionnaire and analyzed through descriptive statistics, paired-samples t-tests, independent-samples t-tests, and effect-size estimation. The findings indicate that students who participated in the PIK-R intervention showed a statistically significant decrease in risk behavior scores compared with students in the control group. The intervention also produced a large practical effect (Cohen's d = 0.85), suggesting that PIK-R can serve as an effective preventive strategy in primary education. This study contributes to the literature by extending evidence on counseling-based risk behavior prevention to early adolescents and by providing context-specific insights from Indonesian schools.